Budgeting in Brazil - Blöndal, Jón R.. (OECD Publishing, 2003)
During his September 2002 visit to OECD Headquarters in Paris, Mr. Guilherme DIAS, the Minister of Planning, Budget and Management, requested the OECD to carry out a review of the Brazilian budgeting system in a similar fashion as it does for its member countries.The OECD responded positively to this request, recognising that Brazil is an established observer of the OECD Working Party of Senior Budget Officials and a key partner in the OECD's overall programme of co-operation with nonmembers